Pengaruh ROE Terhadap Harga Saham PT. Indofood Sukses Makmur Tbk. - Felisia Mileta; Jesa Alexandra Louis; Neyna Maharani Bahtiar; Elizabeth Tiur Manurung (Jurnal Akuntansi, Bisnis dan Ekonomi Indonesia (JABEI), 2024)
This study aims to evaluate the impact of return on equity (ROE) on the stock price of PT Indofood Makmur Tbk over the period 2019-2023. The research method involves analyzing the historical data of the company's ROE and stock prices over the last five years. This data was analyzed using statistical techniques to identify the relationship between ROE and stock prices. The results of the study indicate that ROE does not have a significant impact on the company's stock price, thus rejecting the research hypothesis. The implications of these findings are important for investors in making investment decisions related to the company's stock, highlighting the necessity of considering fundamental factors in investment analysis. This study also supports previous research findings that show ROE does not have a significant influence on the company's stock price.